Implementation of Credit Provision at BRI (Bank Rakyat Indonesia) with Guaranteed Certificate - Yulian Andre Pratama (Sultan Agung Notary Law Review, 2021)
The purpose of this study is to analyze 1). The process of granting credit to the BRI Unit Link Kajen Bank when the guarantee is still a transfer of rights. 2) Obstacles and solutions in the process of granting credit to the BRI Unit Link Kajen Bank when the guarantee is still a transfer of rights. This study uses a sociological juridical approach. The data used are primary and secondary data obtained through interviews and literature study, data analysis is descriptive analytic. The results of the research concluded: 1) The process of granting credit to the BRI Unit Link Kajen Bank at the time of the guarantee there was still a transfer of rights, namely submission of applications, submission of complete documents accompanied by photocopies of the documents for submitting the transfer of property rights to the Land Office, Examination, Analysis of memorandums, approval from branch leadership, execution and disbursement of loans by the Bank to debtors. The process of granting credit to the BRI Unit Link Kajen Bank is carried out by making a written agreement so that it is binding for the parties and becomes a strong evidence base if one day there is a dispute. 2. Constraints and solutions in the process of granting credit to the BRI Unit Link Kajen Bank at the time of the guarantee there was still a transfer of rights, namely the frequent delays in the delivery of notary orders so that the Notary did not have time to check administrative completeness or confirm to BPN due to limited time. Another obstacle is the difficulty of managing the time so that the signing of the deed can be signed together. The solution that can be done is to provide counseling to the bank about the order procedure carried out to a notary and provide understanding to the bank so that the files that have been submitted to the notary have actually been approved by the prospective debtor, both interest and administrative and insurance costs.